2009
DOI: 10.1007/s10886-009-9722-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad Affects Chemical Communication in the German Cockroach, Blatella germanica (L).

Abstract: Spinosad is a biopesticide, derived from fermentation by the soil-dwelling actinomycete, Saccharopolyspora spinosa, which is used to control a variety of insects. Spinosad kills a wide range of insect pests when ingested or topically applied, by overexciting the nervous system, yet is harmless to mammals and many predatory insects. Other modes of action of this insecticide have not been documented. Here, we report that a non-lethal dose of spinosad causes adult male and female German cockroach, Blattella germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Compared to azadirachtin, spinosad presents a higher efficacy against B. orientalis when used for the same period of treatment (Tine et al 2011). The toxicological effect of spinosad confirms previous reports when used against B. germanica (Habachi et al 2009) and Bombus terrestris (2011). Spinosad acts by the physiological perturbation of the target organism (Salgado 1998).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Compared to azadirachtin, spinosad presents a higher efficacy against B. orientalis when used for the same period of treatment (Tine et al 2011). The toxicological effect of spinosad confirms previous reports when used against B. germanica (Habachi et al 2009) and Bombus terrestris (2011). Spinosad acts by the physiological perturbation of the target organism (Salgado 1998).…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that the naturally derived insecticidal spinosad is one among the toxic products 0.072 ± 0.0038 a 0.050 ± 0.0025 b when applied topically against insects Flinn et al 2004;Habachi et al 2009). This product presented a high toxicity against many orders of insects such as Lepidoptera pests (Toews & Subramanyam 2003) and Coleoptera (Galvan et al 2005) and could cause the mortality of the endoparasitoid larvae of Hyposoterdi dymator (Schneider et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insect cuticle is composed of cuticular proteins and chitin, key components of insect exoskeleton and crucial for molting and development [59]. Although cuticular penetration of spinosad is expected to be relatively slow [29], alterations on the arthropod Blattella germanica cuticle hydrocarbon profile due to spinosad exposure have been reported before [60]. The downregulation of cuticle proteins may interfere with cuticle permeability and molting and consequently with the growth and reproduction of arthropods [61].…”
Section: Discussionmentioning
confidence: 99%